2022
DOI: 10.3126/ajms.v13i9.44446
|View full text |Cite
|
Sign up to set email alerts
|

An unattended silent killer: A facility-based cross-sectional study on undiagnosed hypertension from Haryana, India

Abstract: Background: Non-communicable diseases are on the upsurge throughout the world. They take a toll of 71% of overall total death, majorly contributed by cardiovascular disease. Hypertension has been a consistent risk factor for cardiovascular diseases among the various risk factors. Hypertension’s asymptomatic nature makes it a silent killer; many lives are avertable if a timely diagnosis can be assured. Aims and Objectives: The aim of this study was to determine the prevalence of undiagnosed hypertension among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, the major contributing factors for hypertension among adults is body mass index, waist circumference and waist-hip ratio. [17][18][19][27][28][29][30][31]39,40,47,48,53 In the current review, waist circumference and body mass index were revealed to be superior predictors of high blood pressure in Haryanvi Baniyas. On the other hand, Jatts of Haryana had a higher body mass index and waistto-hip ratio which are the major risk factors of hypertension.…”
Section: Risk Factors Of Hypertensionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the major contributing factors for hypertension among adults is body mass index, waist circumference and waist-hip ratio. [17][18][19][27][28][29][30][31]39,40,47,48,53 In the current review, waist circumference and body mass index were revealed to be superior predictors of high blood pressure in Haryanvi Baniyas. On the other hand, Jatts of Haryana had a higher body mass index and waistto-hip ratio which are the major risk factors of hypertension.…”
Section: Risk Factors Of Hypertensionmentioning
confidence: 99%
“…50 It was a l s o observed that adults with high blood pressure and a family record of hypertension were found to have high blood cholesterol and triglyceride levels. 19,31,39,48 Uneducated or illiterate persons were positively associated with hypertension in a meta-analysis undertaken in Southeast Asian countries, which may be attributed to a lower level of awareness among them. 51 Higher education, on the other hand, may promote health literacy and the value of leading a healthy lifestyle, which includes regular physical activity, a wellbalanced diet, and regular screenings to reduce the likelihood of developing hypertension.…”
Section: Risk Factors Of Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations